Parotid swelling and chronic recurrent multifocal osteomyelitis of mandible in children. Issue 1 (January 2015) - Patel, Rajan; Jacob, Roy; Lee, Kenneth; Booth, Timothy N.
Abstract Objective Chronic recurrent multifocal osteomyelitis (CRMO) is an aseptic inflammatory disorder of unknown etiology. CRMO involving the mandible is a diagnostic challenge due to a propensity for solitary involvement and lack of definitive radiologic or pathologic diagnosis. The purpose of this study is to report clinical and imaging findings in cohort of children with CRMO of the mandible. Materials and methods A retrospective search of the Picture Archiving Communication System (PACS) and accompanying reports was performed for studies with suspected osteomyelitis of the mandible. The electronic medical record, histopathology results, and imaging findings were also reviewed. Inclusion criteria included presentation and course as well as surgical biopsy consistent with CRMO. Four children satisfied our inclusion criteria. Mean age was 9.1 years (range 3.5–12). M:F ratio = 1:3. Results Patients presented with mild pain and swelling in the parotid region (n = 4), mildly elevated sedimentation rate (n = 3), and negative biopsy culture (n = 4). A positive response to non-steroidal anti-inflammatory medication was noted in all patients. Imaging demonstrated a predominately sclerotic lesion in the posterior mandible associated with solid periosteal reaction in all patients. Cortical expansion (n = 3) was commonly present. The clinical course was prolonged in the patients in whom a diagnosis of CRMO was not initially entertained. Conclusions Parotid mass or swelling is a common presentation of CRMO involving the mandible. The possibility of this diagnosis should be raised when typical clinical and imaging features are present. Whole body imaging may be helpful to evaluate for additional lesions. While biopsy is necessary with isolated mandibular involvement, repeated biopsies and prolonged antibiotic therapy should be avoided.